DEVELOPMENT OF CREATIVITY AND ARTISTIC TOLERANCE OF FUTURE MUSIC TEACHER - Sobol, Natalia (Continuing Professional Education: Theory and Practice, 2019)
The article deals with question of professional improvement of students in the field of music art pedagogy. Author analyzes the foreign experiencein explanation of creativity in the context of music educational environment.The papers pecifies the relation sandinterin fluences of both “creativity” and “artistictolerance”as professional characteristics of future musicteachers. Also author distinguishes the special aspects of the phenomentrough the prism of the personality creative activities. Artistic tolerance is a respectful attitude of personality toward the diversity of artistic objects, genres, movements etc. In addition, it involves both 1) the relation of future music teacher to the results of creative activities of other people and 2) possibility to express his own views in creative ways. According to the researches of famous western scientists P.Burnard, M. Barrett, D. Elliott and others, artistic tolerance is based on the personality’s artistic accomplishments and experienceas well as creativity. Thus, development of creativity of future music teacher is needed for acquiring his own artistic views, giving him the disengagement from influence of social minds and artistic prejudices. Based on the theory of creativity of M. Csikszentmihalyi, it was defined that creative and tolerant future music teacher might be a) comprehensive and flexible, b) easy in communication without social conflicts, c) ready for dialogue and be self-critical, d) skilled person with strong desire to get new knowledge.Therefore, the author of the current paper considers that the development of the creative personality has a direct connection with the formation of his artistic tolerance.